An effect of the North Atlantic oscillation on the temporal distribution of precipitation: Wavelet expansion method - V. D. Rusov; A. Glushkov; V. Vaschenko; V. Pavlovych; N. Loboda; Zh. I. Patlashenko; V. Khokhlov; A. Svinarenko; T. V. Solonko (Ukrainian Antarctic Journal, 2008)
Within the wave-let expansion method analysis of influence of North-Atlantic oscillation (NAO) on temporal distribution of precipitation on Ukraine is carried out. It is shown that the most large correlation coefficients between NAO indexes and month precipitation sums are defined for the west of Ukraine and for period of the long dominating the single NAO phase.